MARINYO'S ROLE IN NEGERI HUTUMURI, AMBON CITY - Marleen Muskita; Rido Dominggus Latuheru (Journal of Digital Media Communication, 2022)
Culture is a product of human creativity that is very diverse. Hutumuri village is part of the Pata Shiva family which still maintains its customs, one of which is marinyo. Marinyo's role for the community is to channel information from the king by shouting directly to the community. Currently, there are many smartphone applications that can be used as a channel of information to the community, so the role of marinyo is not functioning properly in the customs of the Negeri Hutumuri. The role of the marinyo in the customary land must function optimally, especially by the king who leads the country. The problem studied in this research is the role of marinyo in Negeri Hutumuri by seeing and knowing the role of marinyo in customs in Negeri Hutumuri in Maluku. This study aimed to determine the extent of the role of marinyo in the State of Hutumuri. The scientific approach used in this research is a qualitative descriptive approach where the researcher conducts interviews, observations, and literature studies. Research informants are raja, saniri, and marinyo. The study's results indicate that the role of communication, in this case, carried out by a marinyo is still very necessary. Communication carried out through the State Government (king), to Marinyo, then to the community through tabaos (bataria tita) is still effective because the message conveyed by a Marinyo can be accepted and clearly understood by the community.